Aperçu du statut des Territoires du Nord-Ouest et du Yukon en droit constitutionnel canadien - Melançon, Dominique (Les Cahiers de droit, 1988)
The 1987 Constitutional Accord between the prime minister and the ten provincial premiers has caused discontent amongst the Northwest Territories and Yukon governments. They object to various elements in the Accord which do not confer on them rights identical to those of the provinces, to other elements which are likely to affect their future political evolution and to the fact that the Accord was concluded without their participation. By challenging the Accord before the courts, they have drawn national attention to their status within Confederation. Furthermore, some progress in the status of the Territories was made by the signing of a boundary and constitutional agreement by the Constitutional Assembly of the Western Region and that of Nunavut in Iqaluit on January 15, 1987 for purposes of dividing the Northwest territories. Although the agreement could not be ratified by referendum, it contains the basic principles for guiding the drafting of respective constitutions for the two new entities that will be created. Within the framework of recent events, the author first presents the main stages in the evolution of governmental organization in the Territories and then goes on to analyse their present legal status. This study makes it possible to see if recent evolution will cause the territorial governments increasingly to resemble provincial governments. Nonetheless, in many ways they still remain in a state of dependency vis-à-vis federal authorities. In conclusion, the author observes that the evolution of the Territories with regard to legislative and executive powers and bodies does not mean that they will necessarily obtain provincial status. Their accession to greater political autonomy could possibly become a reality by the implementation of original solutions, distinct from those of southern Canada and better adapted to the specific needs of the North and its important native population.